MARKETING STRATEGY FOR BATIK PRODUCTS IN THE DIGITAL TECHNOLOGY ERA - Samsul Arifin; Jati Jati; Mohamad Rifqy Roosdhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Nowadays, technology is developing faster and faster. This is marked by the use of the internet and digital media. Technology and digital media are able to become an important component for business actors, especially in the batik business sector, to market their products online. Online marketing is considered more profitable because it is able to reach a wide range of potential consumers without space and time limitations. Therefore, online marketing is able to make batik entrepreneurs continue to compete and increase their income. The research method used is qualitative analysis with an exploratory step using participatory observation techniques. The results of this study provide a variety of strategies that can be carried out by business actors including using social media, selling products by utilizing Facebook and Google ads for market share, making E-commerce sales, conducting digital marketing, giving a positive impression of product safety, improving product quality and services, as well as maintaining good relations with consumers or establishing customer marketing relationships, targeting loyal customers, and conducting relevant marketing. The results of this research can be used for business actors because of changing conditions and it is hoped that business actors can survive.